The May 1967 great storm and radio disruption event: Extreme space weather and extraordinary responses. Issue 9 (5th September 2016) - Knipp, D. J.; Ramsay, A. C.; Beard, E. D.; Boright, A. L.; Cade, W. B.; Hewins, I. M.; McFadden, R. H.; Denig, W. F.; Kilcommons, L. M.; Shea, M. A.; Smart, D. F.
Abstract: Although listed as one of the most significant events of the last 80 years, the space weather storm of late May 1967 has been of mostly fading academic interest. The storm made its initial mark with a colossal solar radio burst causing radio interference at frequencies between 0.01 and 9.0 GHz and near‐simultaneous disruptions of dayside radio communication by intense fluxes of ionizing solar X‐rays. Aspects of military control and communication were immediately challenged. Within hours a solar energetic particle event disrupted high‐frequency communication in the polar cap. Subsequently, record‐setting geomagnetic and ionospheric storms compounded the disruptions. We explain how the May 1967 storm was nearly one with ultimate societal impact, were it not for the nascent efforts of the United States Air Force in expanding its terrestrial weather monitoring‐analysis‐warning‐prediction efforts into the realm of space weather forecasting. An important and long‐lasting outcome of this storm was more formal Department of Defense‐support for current‐day space weather forecasting. This story develops during the rapid rise of solar cycle 20 and the intense Cold War in the latter half of the twentieth century. We detail the events of late May 1967 in the intersecting categories of solar‐terrestrial interactions and the political‐military backdrop of the Cold War. This was one of the "Great Storms" of the twentieth century, despite the apparent lack of large geomagnetically induced currents. Radio disruptions like those discussed here warrant the attention of today's radio‐reliant, cellular‐phone and satellite‐navigation enabled world. Key Points: The 23‐27 May 1967 event was a "Great" solar and geospace storm First Air Force Solar Forecasting Unit partially mitigated the impacts of extreme solar radio bursts on U.S. military The storm led to military recognition of space environment effects as an operational concern and helped establish a forecasting system